Targeting NOX2 and glycolytic metabolism as a therapeutic strategy in acute myeloid leukaemia - Carla Ijurko; Marta Romo-González; Rodrigo Prieto-Bermejo; María Díez-Campelo; María-Belén Vidriales; Sandra Muntión; Fermín Sánchez-Guijo; Jesús Sánchez-Yagüe; Ángel Hernández-Hernández (BMC, 2024)
Abstract Acute myeloid leukaemia (AML) is a highly heterogeneous malignancy, with a poor 5-year overall survival rate of approximately 30%. Consequently, the search for novel therapeutic strategies is ongoing, and the identification of new vulnerabilities could accelerate progress. Oxidative stress and metabolic rewiring are established hallmarks of cancer, and recent evidence suggests that NADPH oxidases may regulate metabolism, potentially linking these two processes. Increasing research highlights the importance of NOX2 in AML, particularly its role in metabolic regulation. In this study, we investigated the effects of simultaneously inhibiting NOX2 and glycolysis in AML cells. Dual inhibition of NOX2 and glycolysis-by targeting hexokinase or lactate dehydrogenase (LDH)-significantly reduced cell proliferation, markedly impaired clonogenic potential, and induced extensive cell death in a broad panel of AML cell lines. Importantly, these findings were further validated in primary bone marrow samples derived from AML patients, where combined inhibition triggered similar potent anti-leukemic effects. Furthermore, the combined inhibition of NOX2 and LDH enhanced the efficacy of cytarabine (AraC), suggesting this approach could boost the effectiveness of conventional therapies. In an in vivo AML model, targeting NOX2 and LDH in myeloid progenitor cells delayed the onset of leukaemia and extended survival. In conclusion, our findings propose a novel therapeutic strategy for AML through the dual targeting of NOX2 and glycolysis.